POTENSI WISATA KINAHREJO YANG BERKELANJUTAN, Dusun Kinahrejo, Umbulharjo, Sleman, Yogyakarta - Indrasana, Praba (Universitas Atma Jaya Yogyakarta, 2018)
Abstract: Dusun Kinahrejo has diverse and interesting regional characteristics, with a dynamic regional order in the development of tourist areas. Kinahrejo hamlet is located in an area prone to eruption of Merapi, which is on the slopes of Mount Merapi Umbulharjo village, Cangkringan, Sleman. The declining interest of tourists during the visit in 2015 has an impact on the sustainability of the tourism potential and the economy of the people who rely heavily on the tourism sector. So the passion of the attraction of existing tourism potential needs to be improved and new potential that can increase the interest of tourists to visit. This research uses descriptive qualitative research method. Data were collected through observation, interviews, and documentation. While data analysis is done through (1) data reduction; (2) data presentation; and (3) conclusion/verification. The tourism potential of dusun Kinahrejo is diverse, all of them berinduk on nature tourism (ecotourism); There is a passive and active nature tour: the main attractions enjoy nature as scenery, nature as a sports arena, nature as a vehicle of adrenaline triggers, and there are support tours. The continuity of tourism in dusun Kinahrejo is highly dependent on community participation. Potential development of dusun Kinahrejo has 5 tourism potential, 1) religious tourism and cultural pilgrimage of dusun Kinahrejo, 2) nature tourism, 3) adrenaline tourism, 4) culinary tourism and 5) comunal farming of agro-agricultural.Keywords: tourism potential, area characteristics and sustainabilityAbstraksi: Dusun Kinahrejo memiliki karakteristik wilayah yang beragam dan menarik, dengan tatanan kawasan yang dinamis dalam pengembangan kawasan wisata. Dusun Kinahrejo berada pada kawasan rawan bencana erupsi Merapi, yaitu pada lereng gunung Merapi desa Umbulharjo, Cangkringan, Sleman. Menurunya minat wisatawan dalam kunjungan tahun 2015 berdampak keberlanjutan potensi wisata dan perekonomian warga yang banyak bergantung pada sektor pariwisata. Gairah dan daya tarik potensi wisata yang ada perlu ditingkatkan dan potensi baru yang dapat meningkatkan minat wisatawan untuk berkunjung. Penelitian ini menggunakan metode penelitian deskriptif kualitatif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Sementara itu, analisis data dilakukan melalui (1) reduksi data; (2) penyajian data; dan (3) penarikan kesimpulan/verifikasi. Potensi wisata dusun kinahrejo beragam, semua berinduk pada wisata alami (ekowisata); ada wisata alam pasif dan aktif: wisata utama menikmati alam sebagai pemandangan, alam sebagai arena olahraga, alam sebagai wahana pemicu adrenalin, dan ada wisata pendukung. Keberlanjutan wisata di dusun Kinahrejo sangat tergantung pada partisipasi masyarakat. Pengembangan potensi dusun Kinahrejo memiliki 5 potensi wisata yaitu, 1) wisata religi dan budaya ziarah Kinahrejo, 2) wisata jelajah alam, 3) wisata adrenalin, 4) wisata kuliner dan 5) agrowisata peternakan sapi perah komunal.Kata kunci: potensi wisata, karakteristik wilayah dan keberlanjutan